2017
DOI: 10.22146/jkap.28199
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Land Conversion on Income and Food Security Status For Farmer Households in 5 Villages in Temon Sub-District, Kulon Progo District, 2017

Abstract: Preparation for the construction and development of NYIA airport in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Therefore, the Chinese government continues to focus on the development and expansion of arable land for food crop agriculture in an effort to maintain national food security. Interestingly, Nurpita et al (2017) found that land conversion from agricultural land has negative impacts on household farmer income in Indonesia. Furthermore, the decrease in household farmer income is partly due to the decrease in agricultural land.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the Chinese government continues to focus on the development and expansion of arable land for food crop agriculture in an effort to maintain national food security. Interestingly, Nurpita et al (2017) found that land conversion from agricultural land has negative impacts on household farmer income in Indonesia. Furthermore, the decrease in household farmer income is partly due to the decrease in agricultural land.…”
Section: Resultsmentioning
confidence: 99%
“…Results of their study indicate GDP is a variable having the largest contribution to the dynamics of carbon dioxide emissions in four ASEAN countries. A study by Nurpita A, et al (2017) delves into the impact of land conversion on farmers' income and their food security status. The results show land conversion has a negative and significant effect on their income.…”
Section: The Influence Of Real Gross Regional Domestic Product the Number Of Households The Number Of Non-classified Hotels And Other Typmentioning
confidence: 99%
“…[3] The rate of land conversion from what was originally used for agriculture to housing and industry is unavoidable. [4] Housing and settlements are one of the basic human needs. As mandated in the 1945 Constitution and Article 28 of the 1945 Constitution, housing is one of the basic rights of the people and therefore every citizen has the right to live and to have a good and healthy living environment.…”
mentioning
confidence: 99%